2020
DOI: 10.3390/nu12051522
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tocotrienol-Rich Vitamin E (Tocovid) on Diabetic Neuropathy: A Phase II Randomized Controlled Trial

Abstract: Chronic hyperglycemia increases oxidative stress, activates inflammatory pathways and reduces nerve growth factor (NGF) among diabetic patients, which contribute to development of diabetic peripheral neuropathy (DPN). Tocotrienol-Rich Vitamin E (Tocovid) possesses potent antioxidant and anti-inflammatory properties which are postulated to target these pathogeneses in order to ameliorate DPN. This study aims to evaluate the effects of Tocovid on nerve conduction parameters and serum biomarkers among diabetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…Contrary to these findings, few studies did not find a significant change in levels of TNF between T3 and placebo groups. This can be due to the short duration of the trial or more stable glycemic control of participants as compared to our study (Ng et al, 2020;Tan et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Contrary to these findings, few studies did not find a significant change in levels of TNF between T3 and placebo groups. This can be due to the short duration of the trial or more stable glycemic control of participants as compared to our study (Ng et al, 2020;Tan et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…The results of this study were consistent with most of the RCTs included, indicating a beneficial effect of vitamin E on the incidence of CIPN. This may be explained by the fact that free radical damage caused by chemotherapy plays an important role in the production of CIPN ( Bove et al, 2001 ; Velasco et al, 2016 ; Ahmad Bainmahfouz et al, 2021 ), and supplementation with vitamin E has revealed a potential role in preventing neuropathy in clinical settings ( Rajanandh et al, 2014 ; Ng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…After screening the title and abstract, 73 studies were retrieved for full-text review. From this, 54 studies were excluded, and the reasons for exclusion are presented in the S2 Table . Out of the 19 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] included in the present systematic review, there were four studies [16,17,22,23] involving subjects from two similar datasets, but these studies were included because each study reported unique biomarkers. For other duplicate publications, Pervez et al [30] was selected due to a larger sample size, while Kooyenga et al [25] was selected due to a longer follow-up duration.…”
Section: The Flow Of Study Selectionmentioning
confidence: 99%
“…For other duplicate publications, Pervez et al [30] was selected due to a larger sample size, while Kooyenga et al [25] was selected due to a longer follow-up duration. Thirteen studies [17][18][19][20][21][22][23][24]26,28,30,32,34] reporting CRP or high sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), or malondialdehyde (MDA) were included for meta-analyses.…”
Section: The Flow Of Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation